Risk Management Process Implementation in Warehousing to Enhance the Performance: A Case Study - Hani Khudher Alzahrani (International Journal of Supply Chain Management, 2022)
Managing risks in effective way will grant organizations a competitive edge in the market as the objectives and strategies will be met.  This paper aims to address the risk management process application in warehouses and how that could affect the performance positively if applied correctly. The paper was developed from the review of the literature and a case study of a warehousing organization at Saudi Arabian Oil Company (Saudi Aramco) in The Kingdom of Saudi Arabia. The primary finding was that risk management process implementation provides better performance and gives the management better informed decision making. Also, engaging all people working in the organization will facilitate the process application.